Visions of sainthood in medieval Rome : the lives of Margherita Colonna - Colonna, Giovanni, 1298?-1343 or 1344; Stefania; Field, Larry F.; Knox, Lezlie S.; Field, Sean L. (Sean Linscott), 1970- (University of Notre Dame Press, 2017)
In Visions of Sainthood in Medieval Rome, Larry F. Field, Lezlie S. Knox, and Sean L. Field present the first English translations of Margherita Colonna's two ""lives"" and a dossier of associated texts, along with thoroughly researched contextualization and scholarly examination.